The New Zealand guidance counsellor : an analysis of actual role performance : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education at Massey University - Chua, Charles Siak-Thye (Massey University, 1980)
Guidance and counselling services have been an important feature of the New Zealand secondary education system for two decades now. However, there have been few official policy statements and little research on the subject, hence an adequate definition and prescription for the role of the guidance counsellor has not been produced. What type of work guidance counsellors do and how they perform their jobs has never been suitably examined in this country and it is something little known even to those who are actually involved in the service. What is known has been restricted to propositions provided by literature, which generally states what and how guidance counselling ought to be carried out, but rarely what is actually taking place. The actual role performance of guidance counsellors has been sought mostly by means of questionnaire survey studies. The present study made a day-to-day recording of the activities and the time allocated to the various activities of three practising guidance counsellors in three New Zealand secondary schools. The recording was carried out from June to August, 1979. Each counsellor was requested to make a detailed daily recording of all the activities undertaken and the amount of time spent on them. These records were then collected from the counsellors at the end of each week; the materials were collated and arranged into various categories and the amount of time for each was calculated. Comparisons were made among the three guidance counsellors in the activities undertaken and some comparison was also made with a comprehensive New Zealand questionnaire study. The overall results showed that the three guidance counsellors were involved in similar work patterns and about a third of their activities were in educational, vocational, and personal-social guidance areas which involved direct contacts with pupils whilst the remaining activities involved administrative duties, staff liaison, liaison with various supporting services, and a series of other minor responsibilities. Each counsellor, besides sharing the similar work patterns, was involved in some areas of activity which were unique from the other two. The counsellors had working weeks of lengthy duration which also included work done during the weekends. Although the period of the study was relatively short and involved only one part of the year, together with the fact that only three counsellors were studied, the results, nevertheless, provide a systematic and complete account of the actual role performances of these counsellors. In this way they provide a comprehensive account of what is actually being done by a selection of people in this important school position. The aims of this study were to achieve a better understanding of the role of guidance counsellors and to help overcome the vagueness usually associated with descriptions of the guidance counsellor's role.
Keywords: Student counsellors; School counsellors, New Zealand; Guidance counsellors; Secondary school counselling